PEMBELAJARAN LARI JARAK PENDEK DENGAN MENGGUNAKAN PENDEKATAN BERMAIN HITAM HIJAU PADA SISWA KELAS III SD NEGERI CAWITALI 03 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this research was to determine whether learning outcomes sprinting through play approach canimprove student learning outcomes. This research is a class act consisting of two cycles where each cycle consistsof four stages: planning, action, observation (observation) and reflection. Data collection techniques in thisstudy using the test observation of student performance, test observations of student activity, sprinting learningoutcomes, as well as the questionnaire used to determine students' responses to the learning model sprints to theapproach play. Observed data psychomotor performance results obtained in the first cycle of 79.4%, while in thesecond cycle results obtained 81.5%. Affective observation data obtained in the first cycle results in cycle II78.7% 87.1% obtained results. Data results of student responses obtained results of the first cycle second cycle90.60% 92.0% obtained results, the results of the first cycle sprint in 8.4 seconds while the second cycle of 7.5seconds. The conclusion of this research is to approach playing Penjasorkes learning can improve studentlearning outcomes. While the suggestions in this research is to study the learning model Penjasorkes throughplay approach can be used as an alternative learning model Penjasorkes so as to create an attractive learningmodel for students so that students are more enthusiastic about learning